COVID-19: Impact of the Pandemic on Children’s Lives - Roquette, Margarida (2023)
Introduction: The COVID-19 pandemic has had a considerable impact on the biopsychosocial elements of human beings, especially children and teenagers, as vulnerable groups. Social isolation can lead to psychiatric illness, obesity, and sleep disorders in adults. This study aimed to determine the impact of lockdown on children’s sleep, diet, physical activity, and behavior. Methods: This was a retrospective observational study conducted from May 1, 2020, to March 31, 2021. Data were collected from four healthcare centers in Cascais (Lisbon, Portugal) by administering a questionnaire in person and online. Descriptive statistical analysis was conducted using Microsoft Excel® and the SPSS® software (version 23). Results: In total, 790 responses were collected (median age 9 years old) without gender predominance. Family routine and behavioral changes were found in 84% and 63% of children, respectively. In addition, dietary changes were observed in 43% of them, with 62% reporting an increase in quantities and 23% reporting weight gain (more than 5 kg in 18%). Regarding physical activity, 44% exercised more than three times a week before the lockdown. Following COVID-19, 18% maintained this routine, and 48% quit sporting activities. Finally, sleep changes occurred in 42%, including nightmares and difficulty falling asleep. Discussion: Childhood and adolescence are periods of considerable social and psychomotor development, and any routine disruption can cause profound changes in personal and interpersonal experience during this period. The findings of this study revealed that lockdown caused changes in children’s behavior, diet, physical exercise, and sleep. It is essential to outline strategies to support children and teenagers with a multidisciplinary approach to reduce the effects of social isolation on their development.